Covid-19 and its implications for the biopsychosocial aspect of the elderly: what is the price of the pandemic for the elderly population? (Research, Society and Development, 2023)
COVID-19, declared a pandemic in March 2020, showed that the most vulnerable age group is the elderly population. In view of this, the article aims to highlight the impact caused by COVID-19 on the elderly. For the study, a literature review was used, using the clinical question: “Has the pandemic impacted the quality of life of the elderly, in terms of the biopsychosocial aspect?”. To respond, the following databases were used: Google Scholar, Bireme, Scielo, EBSCO and pubmed. As inclusion criteria, it was observed: articles written in Portuguese and English, published in the last 5 years, that addressed the researched topic and available electronically in full format, and as exclusion criteria, articles that did not meet the inclusion criteria were excluded. Subsequently, it was observed as results and discussion that social distancing aggravated the mental and physical health of the elderly, the lack of family life directly impacted the well-being, the fear of contamination and death from the virus made many elderly people became increasingly depressed, and that food security, physical activity and nutrition were also compromised. Finally, the conclusion shows that one must consider not only the physical aspect of the disease, but also the psychological and social aspects, which make up the biopsychosocial model, which shows us the complexity of the disease and how vulnerable populations can experience the effects of this.